Marketing Strategy Factors And Product Quality: Implications On Purchase Decisions At The Wahidin Bagan Bilah Spare Part Shop - Suhaimah Afifah; Zufrie Zufrie; Mulya Rafika (International Journal of Economic Research and Financial Accounting, 2025)
This research aims to analyze the influence of marketing strategy and product quality on consumer purchasing decisions at the Wahidin Bagan Bilah Spare Parts Store. The main problem raised is how marketing strategy and product quality partially or simultaneously influence purchasing decisions. The research method used is quantitative with an associative descriptive approach. The population in this research is consumers of the Wahidin Bagan Bilah Shop, the exact number of which is not known. The sampling technique uses the method non-probability sampling with approach incidental sampling, and the number of respondents determined was 96 people, based on the Cochran formula. Data collection was carried out through questionnaires, interviews and observations. Data analysis uses multiple linear regression which is supported by the classical assumption test, t test, F test, and coefficient of determination. The research results show that both marketing strategy and product quality have a positive and significant partial or simultaneous effect on purchasing decisions. The coefficient of determination value of 73.1% indicates that the marketing strategy and product quality variables together are able to explain purchasing decisions, while the remainder is influenced by other factors outside the research model.